Penerapan Pajak Penghasilan Pasal 4 Ayat (2) Dalam Sistem Pepajakan Indonesia - Siti Nurlina Nasution; Lola Kesuma Pardosi (GLOBAL SCIENTS PUBLISHER, 2026)
The objective “of this study is to examine the concept, legal basis, mechanism, and implementation of Income Tax (PPh) Article 4 Paragraph (2) within the Indonesian tax system. The method employed is a qualitative normative approach utilizing a literature review with secondary data drawn from primary, secondary, and tertiary legal sources. The results of the study indicate that Article 4(2) of the Income Tax Law is a final tax imposed directly at the time of the transaction at a specific rate without considering total income. This tax offers advantages in terms of simpler administration and ease of collection through a withholding tax system. Taxable items include deposit interest, prizes, stock transactions, transfers of land and buildings, construction services, and rent for land and buildings. However, many obstacles remain in its implementation, including a lack of knowledge among taxpayers, errors in the application of rates, and limitations in the tax administration system. Consequently, for the successful implementation of Income Tax Article 4 Paragraph (2), increased public awareness, strengthened administrative systems, and better oversight”are required.